2018
DOI: 10.1038/s41467-018-05067-x
|View full text |Cite
|
Sign up to set email alerts
|

Human pluripotent reprogramming with CRISPR activators

Abstract: CRISPR-Cas9-based gene activation (CRISPRa) is an attractive tool for cellular reprogramming applications due to its high multiplexing capacity and direct targeting of endogenous loci. Here we present the reprogramming of primary human skin fibroblasts into induced pluripotent stem cells (iPSCs) using CRISPRa, targeting endogenous OCT4, SOX2, KLF4, MYC, and LIN28A promoters. The low basal reprogramming efficiency can be improved by an order of magnitude by additionally targeting a conserved Alu-motif enriched … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 52 publications
3
117
0
1
Order By: Relevance
“…We designed guide RNAs for the LEUTX promoter and putative novel enhancer regions (Extended Data Fig. 5e) to experimentally test these using the CRISPRa activation system 19 in HEK293 cells. The expression level of LEUTX nearly doubled when the guide RNAs targeting the promoter region were transfected together with the putative enhancer 1 targeting guide RNAs in comparison to the promoter targeting guide RNAs only (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We designed guide RNAs for the LEUTX promoter and putative novel enhancer regions (Extended Data Fig. 5e) to experimentally test these using the CRISPRa activation system 19 in HEK293 cells. The expression level of LEUTX nearly doubled when the guide RNAs targeting the promoter region were transfected together with the putative enhancer 1 targeting guide RNAs in comparison to the promoter targeting guide RNAs only (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CRISPR-activation (CRISPRa) is a potent tool for selective transcriptional upregulation of endogenous genes, which functions by targeting a dead Cas9 (dCas9) with transcriptional co-activators to gene promoters using short-guide RNAs (sgRNAs) (Cheng et al 2013.;Gilbert et al 2014;Chavez et al 2015;Konermann et al 2014), and has been successfully used for cellular reprogramming and the study of cellular transitions (Chakraborty et al 2014;Black et al 2016;Peng Liu et al 2018;Weltner et al 2018;Yang et al 2019;Genga et al 2019). CRISPRa is preferable to traditional overexpression techniques, such as cloned cDNA overexpression, as it leads to target gene activation at physiologicallyrelevant levels (Chavez et al 2015;Sanson et al 2018;Yang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Two components of the oriP and Epstein-Barr nuclear antigen-1 (EBNA-1) are also used widely in episomal plasmids [32][33][34][35][36][37][38] . Yu et al reported that human iPSCs that are completely free of plasmids and transgene sequences could be derived from fibroblasts by a single transfection with oriP/ EBNA-1-based episomal plasmids [39][40][41][42] .…”
Section: Non-integrative Methods Of Ipsc Productionmentioning
confidence: 99%